2003
DOI: 10.1079/phn2003505
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and validity of a food-frequency questionnaire for use among low-income Brazilian workers

Abstract: Objectives: To assess the reproducibility and validity a 127-item, habitual intake, foodfrequency questionnaire (FFQ), developed for low-income and low-literacy Brazilian workers, by comparison with a 24-hour dietary recall (24-HDR). Design: The FFQ and 24-HDR were interviewer-administered at the local workplace to each subject twice, with a period of 6 months between estimates; and four 24-HDRs were conducted during the 4-month period between the two FFQs (FFQ1 and FFQ2). Reproducibility was tested by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
33
3
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 26 publications
11
33
3
13
Order By: Relevance
“…The energy adjustment resulted nevertheless in a reduction in correlation coefficients for most nutrients, confirming previous findings 8,22 . The total energy adjustment was performed on the assumption that each participant reported similar nutrient intakes in both questionnaires 4 .…”
Section: Nutrientssupporting
confidence: 80%
“…The energy adjustment resulted nevertheless in a reduction in correlation coefficients for most nutrients, confirming previous findings 8,22 . The total energy adjustment was performed on the assumption that each participant reported similar nutrient intakes in both questionnaires 4 .…”
Section: Nutrientssupporting
confidence: 80%
“…The average correlation coefficient for the entire population studied was 0.52 23 . In another validation study conducted in Brazil, Fornes et al 26 found an average correlation coefficient of 0.50 for a population of adults; the same value that was found in the present study (0.50) for energy-adjusted coefficients.…”
supporting
confidence: 77%
“…Compared with an FFQ validation study among 104 Brazilian workers (23) , the present study demonstrated a slightly higher mean de-attenuated correlation coefficient for energy and the five nutrients in common between the two studies (0?42 v. 0?44).…”
Section: Discussioncontrasting
confidence: 78%